The chemical reactivities of DOPA and dopamine derivatives and their regioselectivities upon oxidative nucleophilic trapping. Issue 41 (13th October 2016) - Cheah, Yong Shung; Santhanakrishnan, Sridhar; Sullivan, Michael B.; Neoh, Koon Gee; Chai, Christina L.L.
Abstract: The chemical reactivities of four catecholamines, N -acetyl dopamine (NADA) and its dehydro derivative (NAΔDA), N -acetyl 3, 4-dihydroxy-phenylalanine methyl ester (NADOPAME) and its dehydro derivative (NAΔDOPAME), under oxidative nucleophilic trapping and polymerisation conditions were compared and contrasted. Despite their structural similarities, varying reactivities and regioselectivities for oxidative nucleophilic trapping with ethanethiol were observed. This has possible implications on the use of these natural building blocks and their derivatives in the design and synthesis of biomimetic materials. Graphical abstract: